Evaluation of the effectiveness of different remineralization agents on primary and permanent teeth exposed to acidic liquids: a randomized controlled in vitro study - Bilge, Kubra; Ipek, Irem; Eskibaglar, Busra Karaagac (Bmc, 2025)
Background The aim of this study is to evaluate the effectiveness of different remineralization agents applied to primary and permanent teeth that were demineralized in acidic environments with varying pH levels, using scanning electron microscopy (SEM) and microhardness measurements. Methods In this study, 80 primary second molars and 80 permanent premolars were used and demineralization procedure was applied by keeping in gastric acid (pH = 1.2) and kefir (pH = 4.5) for 72 h. Then, samples were randomly divided into groups (n = 10) to be applied with different remineralization agents (Curodont Protect, MI Paste Plus, Tooth Mousse) for 14 days. Samples in the control group were kept in artificial saliva for 14 days. Microhardness measurements were made at the beginning, after the demineralization procedure and after the remineralization procedure from all groups and SEM analyses were performed on one sample from each group. Since the assumptions of parametric test were met in the evaluation of the data (Kolmogorov-Smirnov), two-way ANOVA, followed by the Tukey post hoc test. p < 0.05 was accepted as the significance value. Results The lowest microhardness values and the most eroded areas in SEM images were observed in primary teeth. When acidic liquids were evaluated, microhardness values decreased more in those immersed in gastric acid than at the initial. After the application of remineralization agents, the microhardness values of primary and permanent teeth increased the most in the Curodont Protect group and the least in the control group. In SEM images, the most eroded areas were observed in the control group in which no remineralization agent was applied after immersed in gastric acid in primary teeth. Conclusion Gastric acid is a stronger acid compared to kefir, which may explain its more erosive effect on both primary and permanent teeth. Curodont Protect, a biomimetic peptide-based product, can be preferred primarily in clinical use for erosive enamel treatment because it shows an effective remineralization ability on eroded enamel.
Keywords: Remineralization agents; Primary and permanent teeth; SEM; Microhardness